Insulin autoimmune syndrome induced by methimazole in a Korean girl with Graves' disease - Sun Hee Lee; Seung Hwan Oh; Woo Yeong Chung (Korean Society of Pediatric Endocrinology, 2013)
Hypoglycemia was detected in a 15-year-old girl due to loss of consciousness. She was diagnosed with Graves' disease and was being treated with methimazole for the past 4 months. A paradoxically increased insulin levels was found when she suffered from the hypoglycemic episode. An imaging study showed no mass lesion in the pancreas, and insulin antibodies were found in the serum. She was diagnosed with insulin autoimmune syndrome. Her HLA typing was performed, and it revealed HLA-DRB1 *04:06. The patient was treated with a corticosteroid for 2 months. After discontinuing the steroid, the insulin antibody titer decreased dramatically, and she did not have any episode of hypoglycemia since. This is the first report of insulin autoimmune syndrome in a Korean girl, and we have revealed the connection between HLA type and insulin autoimmune syndrome in Korea.